Comparison of Motivation Levels of Outdoor and Indoor Athletes Studying Physical Education and Sports Training - Levent Ceylan; Eda Bilen; Murat Eliöz; Hamza Küçük (Journal of Educational Issues, 2024)
Purpose: The fact that the sports branch that the athletes are interested in is included in the group of indoor and outdoor sports or team and individual sports can create differences in the motivation levels of the athletes. In this study, it was aimed to compare the motivation levels of team and individual athletes who do sports in Indoor and Outdoor. Method: The Sports-Specific Achievement Motivation Scale (SSAMS) developed by Willis (1982) was used to determine the motivation levels of the athletes in the study. The study consists of athletes who take part in Archery, Athletics, Judo, Tennis, Muaythai, Shooting (Weapon), Volleyball, Football, Basketball, Handball and Field hockey teams in Turkey. A total of 259 athletes, 170 men and 89 women, in these teams were included in the study. Findings: When we compared the motivation levels of individual and team athletes, a significant difference was found in the sub-dimensions of “motivation to show strength”, “motivation to approach success” and “avoiding failure” (p < 0.05). While a significant difference in the sub-dimensions of “motivation to show strength” and “motivation to approach success” was in favor of team athletes, “motivation to avoid failure” was found in favor of individual athletes (p < 0.05). Motivation levels of indoor and outdoor athletes. A significant difference was found in the motivation sub-dimensions of “motivation of strength” and “motivation of avoiding failure” of indoor and outdoor athletes (p < 0.05). It is seen that the significant difference is in favor of indoor athletes. Result: As a result; It has been determined that the sports branch differences that the athletes are interested in, the aims of their orientation to sports, the level of communication between the athletes studying physical education and sports training and the people who are in direct and constant communication, and the spatial differences in which the interested sports branch is performed can play an active role in the motivation levels of the athletes. The scarcity of studies on athletes in different branches doing sports in indoor and outdoor areas in the literature has shown that more studies are needed in this area.